How a Metaphor Inspired by Formula 1 Motor Racing Can Help Enhance the Work of a Social Inclusion Community Center - Peter R. J. Trim; Yang-Im Lee (Businesses)
Not-for-profit organizations provide a range of services that satisfy the needs of individuals and help a community to be sustainable. To explain how staff based at a social inclusion community center contribute to social impact, we undertake a case study and incorporate the stakeholder approach that draws on the activities of Pembroke House in south London. Pembroke House engages in social action and provides a number of services considered beneficial to the local community it serves. By adopting this approach, we place emphasis on how the value co-creation concept, which is reinforced by the social marketing approach, helps staff to provide different forms of intervention that ultimately give rise to trust-based relationships involving those providing the service and those receiving the service. To explain this, we make an analogy between a Formula 1 motor racing team servicing a car during a pit-stop while competing in a grand prix and a vulnerable person who visits a food bank seeking assistance in the form of a food parcel. Through the process of drawing on the use of metaphors and making a link with Formula 1 motor racing, we elucidate the value co-creation process and reveal how the social impact provision provided by Pembroke House can be intensified through the deployment of the stakeholder approach, which gives rise to a social inclusion community center partnership framework.